Accessing the molecular frame through strong-field alignment of distributions of gas phase molecules - Reid, Katharine L. (Royal Society of Chemistry, 2018)
A rationale for creating highly aligned distributions of molecules is that it enables vector properties referenced to molecule-fixed axes (the molecular frame) to be determined. In the present work, the degree of alignment that is necessary in order for this to be achieved in practice is explored. Alignment is commonly parametrised in experiments by a single parameter, <cos²Θ>, which is insufficient to enable predictive calculations to be performed. Here it is shown that, if the full distribution of molecular axes takes a Gaussian form, this single parameter can be used to determine the complete set of alignment moments needed to characterise the distribution. In order to demonstrate the degree of alignment that is required in order to approach the molecular frame, the set of alignment moments corresponding to a few chosen values of <cos²Θ> are used to project a model molecular frame photoelectron angular distribution into the laboratory frame. These calculations show that <cos²Θ> needs to approach 0.9 in order to avoid significant blurring to be caused by averaging.